Tests of Conditional Asset Pricing with Time-Varying Moments and Risk Prices - Turtle, Harry; Buse, Adolf; Korkie, Bob (Journal of Financial and Quantitative Analysis, 1994)
Harry Turtle, Adolf Buse, Bob Korkie, Tests of Conditional Asset Pricing with Time-Varying Moments and Risk Prices, The Journal of Financial and Quantitative Analysis, Vol. 29, No. 1 (Mar., 1994), pp. 15-29